Effects of Different Levels of L-carnitine Supplementation on Egg Quality and Blood Parameters of Laying Japanese Quail - Parizadian, B.; Ahangari, Y.J.; Shargh, M. Shams; Sardarzadeh, A. (International Journal of Poultry Science, 2011)
The objective of present study was to investigate the effects of various levels of L-carnitine on performance, egg quality and blood parameters of laying Japanese quail. This experiment was carried out using 128 quail in a completely randomized design with four levels of L-carnitine (0, 125, 250 and 500 mg/kg). Four replicates with 8 quails were allocated to each experimental treatment and birds were reared from 35-70 days. The results showed that there were no significant differences in feed intake and egg production among experimental treatments (p>0.05). The effect of L-carnitine on feed conversion ratio was significant (p